PENGARUH MOTIVASI DAN PRESTASI KERJA TERHADAP KINERJA KARYAWAN PT PENDAR KAPITAL SEJAHTERA - Tini Juartini (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This research comes from the formulation of the problem which aims to determine the effect of motivation and work performance on employee performance at PT Pendar Kapital Sejahtera. This type of research is a type of quantitative research using survey methods and data collection. In this study, researchers used a questionnaire in the form of written questions given to respondents and distributed to all employees of PT Pendar Kapital Sejahtera as many as 40 respondents. Through the distribution of data collection techniques kuisioner. litert scale by calculation. esting exercise research instruments, test data the classic, assumption and test a hypothesis.